Movement Education Roll Depan Terhadap Pengembangan Kemampuan Gerak Dasar Motorik Anak - Anisa Sutarman; Asma Bara; Asep Angga Permadi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to examine the influence of a Movement Education approach based on forward rolls on the development of children's basic motor skills. This research utilizes Classroom Action Research (CAR) following the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages involving 20 students at SDN 1 Sukagalih. Data were analyzed using descriptive statistics, paired sample t-tests, and normality tests. The results showed a significant improvement in motor performance; the average running score increased from 56.85 to 84.55, and throwing from 35.00 to 57.00. Statistical analysis confirmed significant differences in the running and throwing variables (p < 0.05), although the jumping variable did not show a statistically significant change (p = 0.914). The Movement Education approach effectively improves basic motor skills, particularly in coordination and agility, through active and explorative learning experiences. Theoretically, this study supports the integration of movement education concepts into physical education. Practically, the modification of tools—such as inclined mats—can overcome facility limitations and increase student confidence, making it a recommended innovative model for elementary school physical education. Keywords: Basic Motor Skills, Movement Education, Forward Roll